The Everglades : an environmental history - McCally, David, 1949- (Florida history and culture series., 1999)
"This work for general readers and environmentalists alike offers the first major discussion of the formation, development, and history of the Everglades, considered by many to be the most endangered ecosystem in North America. Comprehensive in scope, it begins with south Florida's geologic origins - before the Everglades became wetlands - and continues through the twentieth century, when sugar reigned as king of the Everglades Agricultural Area."--BOOK JACKET. "Charting the effects of human intervention on the region, David McCally traces its habitation from the Calusas and other native groups to the modern period dominated by agri-business."--Jacket.